Addressing climate-action implementation gaps in cities: planning for meaningful and consistent implementation through the 5-UP framework - Diaz, Catalina; Tajuddin, Nilofer; Deshayes, Eloïse; Chelleri, Lorenzo; Vera, Constanza; Aili, Federico; Kapetas, Leon (Frontiers in Sustainable Cities, 2025)
Achieving climate objectives in cities requires a significant acceleration of current efforts and deep structural changes in how policies, programs, and projects are implemented. Despite commitments to climate action at the local level, cities continue to face challenges in delivering tangible outcomes, as implementation is project-led, output oriented, and siloed. Climate policy and planning frameworks often articulate ambitious cities visions and agendas, sometimes supported by funding schemes, yet falling short in translating these objectives into consistent implementation pathways. This study proposes the 5-UP Framework, a new methodological approach to respond to implementation gaps in climate action, fostering consistent and systemic action in cities. The framework has been built after assessing existing literature, climate plans, and implementation barriers across ten European cities using structured surveys, workshops, and focus groups. The findings revealed that these gaps can occur before, during, and after action is carried out. To address this, the 5-UP Framework links implementation to five dimensions: UPDATING city needs aligned with actions, UPSKILLING knowledge and agents of change, UPGRADING through piloting, embedding UPSCALING of actions, and UPTAKING key mechanisms and knowledge. With cities' growing awareness of climate change impacts and persistent implementation gaps, this paper shows that support should extend beyond financing and project outputs. It should also guide capacity building, human agency, prototyping, and upscaling to mainstream climate action systemically.